Creole magazines and Creole intellectuality: The broad debate on Argentinian national tradition - Minelli, Ivia (2021)
The purpose of this essay is to review the discussion on the Argentinian national tradition between 1890 and 1910 from the analysis of Creole and its branches. Creole magazines being a part of popular journalism during the independence centenary will be analyzed. These magazines are mainly preserved in Robert Lehmann-Nitsche archives (Ibero-Amerikanisches Institut, Berlin) classified as folklore since 1897. So the analysis of their programs is the main purpose of this essay in order to study their editorial context and its specificity; the result is the recovery of a speech that was overshadowed.